Eosinophilic Fasciitis with Hypereosinophilia as the Initial Clinical Manifestation of Peripheral T-Cell Lymphoma, Not Otherwise Specified - Okuyama, Shuhei; Satomi, Hidetoshi; Ishikawa, Ryuto; Shishido, Tsutomu; Sato, Keijiro; Ueki, Toshimitsu; Sumi, Masahiko; Kobayashi, Hikaru (Internal Medicine, 2022)
A 58-year-old man presented with painful edema of the extremities, and a diagnosis of eosinophilic fasciitis (EF) was confirmed. He also met the criteria for hypereosinophilic syndrome (HES), but there were no findings suggestive of malignancies or hematologic neoplasms despite a close examination. He was started on steroid therapy but subsequently developed severe liver dysfunction, hemophagocytic lymphohistiocytosis, hepatosplenomegaly, and renal involvement. The diagnosis of peripheral T-cell lymphoma, not otherwise specified was finally established by a bone marrow reexamination and liver biopsy. In cases of eosinophilia, EF, and/or HES, it is important to suspect an intrinsic abnormality, including potential T-cell lymphoma.